1999
DOI: 10.1104/pp.119.4.1457
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a Gibberellin-Induced RNase Expressed in Barley Aleurone Cells1

Abstract: We cloned a cDNA for a gibberellin-induced ribonuclease (RNase) expressed in barley (Hordeum vulgare) aleurone and the gene for a second barley RNase expressed in leaf tissue. The protein encoded by the cDNA is unique among RNases described to date in that it contains a novel 23-amino acid insert between the C2 and C3 conserved sequences. Expression of the recombinant protein in tobacco (Nicotiana tabacum) suspension-cultured protoplasts gave an active RNase of the expected size, confirming the enzymatic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…Besides ethylene, other plant hormones, like auxins and gibberellins, appear to be triggering agents for expression of several important genes. In relation to starch-metabolizing enzymes, the effects of GA 3 on a-amylase expression and secretion from the aleurone layer of cereals are well known (Rogers and Rogers 1999). However, there is lack of information for fruits, regarding starch-metabolizing enzymes and plant hormones during ripening.…”
Section: Discussionmentioning
confidence: 99%
“…Besides ethylene, other plant hormones, like auxins and gibberellins, appear to be triggering agents for expression of several important genes. In relation to starch-metabolizing enzymes, the effects of GA 3 on a-amylase expression and secretion from the aleurone layer of cereals are well known (Rogers and Rogers 1999). However, there is lack of information for fruits, regarding starch-metabolizing enzymes and plant hormones during ripening.…”
Section: Discussionmentioning
confidence: 99%
“…In tomato, the strongest DELLA-independent induction by GA was on a ribonuclease (RNase) gene (Solyc05g007950.2, 15-fold change). A previous study in barley aleurone identified RNase as a GAinduced gene (Rogers and Rogers, 1999). Tomato GA-regulated genes include homologs of well-characterized Arabidopsis genes: GA downregulated, such as GA20ox, GID1, and SCL, and GA upregulated genes, such as GASA-like (GAST1) and EXPANSIN (Shi et al, 1992;Chen et al, 2001;Zentella et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Secretion of RNases from the embryo and aleurone into the endosperm during germination (Barker et al, 1974;Rogers and Rogers, 1999) is thought to aid mobilization of stored RNA. The induction of S-like RNases by senescence in Arabidopsis (Taylor et al, 1993;Bariola et al, 1994) and tomato (Lers et al, 1998), and by phosphate (Pi) starvation in several plant species (Taylor et al, 1993;Bariola et al, 1994;Kö ck et al, 1995;Dodds et al, 1996) suggests a role in nutrient recycling that comprises scavenging Pi from RNA.…”
mentioning
confidence: 99%
“…The ZEN1 nuclease was even demonstrated to be responsible for degradation of nuclear DNA during PCD of tracheary elements (Ito and Fukuda, 2002). RNases have been reported to be induced in PCD processes, such as tracheary element differentiation (Thelen and Northcote, 1989;Ye and Droste, 1996), aleurone cell death (Rogers and Rogers, 1999), and endosperm development (Young and Gallie, 2000). The PCD-associated RNases might be part of the death execution machinery or may be responsible for removal of RNA from the dying cells.…”
mentioning
confidence: 99%